2006
DOI: 10.1007/s10142-005-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to the identification and characterisation of protein composition in wheat germ

Abstract: Proteome analyses were carried out on commercial wheat germ of mature grain from the biscuit-making wheat cultivar, Rosella. Wheat germ protein extracts were fractionated by two-dimensional gel electrophoresis across two different immobilised pH gradients: pH 4.0-7.0 and 6.0-9.0. A total of 612 individual protein spots were excised from the gels and characterised by peptide mass fingerprinting. From these analyses, 347 individual proteins were identified from protein sequence database interrogation, and 301 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…However, the major protein class in terms of spot number (387 spots or 58%) was identified as the 7S globulin storage protein (globulin 3 protein) of the cupin superfamily. Although previously reported in wheat grain (Robert et al, 1985), this protein was not identified as a component in the endosperm (Skylas et al, 2000) or germ (Mak et al, 2006) and has not been localized in wheat grain. It has been speculated that in addition to their storage protein function, 7S globulins may offer some protection against oxalic acid (Dunwell et al, 2000) produced by pathogenic fungi (Donaldson et al, 2001;Lane, 2002).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, the major protein class in terms of spot number (387 spots or 58%) was identified as the 7S globulin storage protein (globulin 3 protein) of the cupin superfamily. Although previously reported in wheat grain (Robert et al, 1985), this protein was not identified as a component in the endosperm (Skylas et al, 2000) or germ (Mak et al, 2006) and has not been localized in wheat grain. It has been speculated that in addition to their storage protein function, 7S globulins may offer some protection against oxalic acid (Dunwell et al, 2000) produced by pathogenic fungi (Donaldson et al, 2001;Lane, 2002).…”
Section: Discussionmentioning
confidence: 64%
“…Their location within the grain has not been identified explicitly and is usually assumed to be in the endosperm (Gebruers et al, 2001). Other reported proteomic analyses of wheat grain did not identify these proteins in the endosperm (Skylas et al, 2000) or embryo (germ; Mak et al, 2006), suggesting that they are likely to be exclusively located in the bran. Our proteomic and confocal immunomicroscopy results show that XIP-I is highly concentrated within the nucellar layer (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from separate proteomic analyses of developing wheat ) and rice (Xu et al 2008) endosperm, and wheat (Mak et al 2006) and rice embryos (Woo et al 2002;Wang et al 2008) highlight the differences in these two seed organs (Table 1). The CM proteins were the most abundant in all instances; however, members of the PF category were relatively more abundant in endosperm, while proteins included in the SR and HS categories were more abundant in embryos.…”
Section: Endosperm Developmentmentioning
confidence: 92%
“…Using a 2-DE plus either MALDI-TOF PMF (Finnie et al 2002;Vensel et al 2005;Finnie and Svensson 2009) or LC-MS/MS (Méchin et al 2004;Mak et al 2006;Xu et al 2008;Kim et al 2009) experimental design, a total of 1,496 proteins were identified. When the proteins are separated into the same 10 functional classes that have been used throughout, the distribution is as follows: CM, 34%; CS, 12; SR, 5; NA, 2; PS, 2; PF, 5; PT, 7; HS, 2; MT, 2; and PUF, 29.…”
Section: Endosperm Developmentmentioning
confidence: 99%